The Role of Modern Methods of Accounting Management in Supporting Competitiveness (Study Exploratory the Opinions of Managers Sections of Categories in the Iraqi Economic Units) - Faten H. Al –Fadhel; Mohammed A. Al–Shammari (Journal of Madenat Alelem University College, 2021)
The main objective of this research is to demonstrate the role of applying modern methods of administrative accounting in achieving and supporting the competitiveness of economic units to maintain their continuity in their competitive environment. To achieve this objective, the descriptive analytical method was used by using the questionnaire form to analyze the opinion of the research sample in the statement of the role of these methods in supporting competitiveness, the results of the research showed that the Iraqi industrial environment is characterized by special circumstances that require the development of the necessary capabilities to keep pace with developments in the competition environment, and that the Iraqi economic units strive to provide distinct products in terms of quality and prices The results showed that the management has sufficient knowledge of the modern methods of administrative accounting under study, and that the application of these methods has a significant role in achieving the competitiveness and competitiveness of the economic unit, and in the light of the above recommended research focus economic units on the application of modern methods of modern accounting to meet the requirements of customers by providing a distinct product in terms of quality and price at the lowest cost and dissemination of cultural and advertising awareness of local products.